Extracellular Synthesis and Characterization of Gold Nanoparticles Using Mycobacterium sp. BRS2A-AR2 Isolated from the Aerial Roots of the Ghanaian Mangrove Plant, Rhizophora racemosa - Camas, M.; Sazak Camas, A.; Kyeremeh, K. (Springer India, 2018)
Through the use of genomes that have undergone millions of years of evolution, marine Actinobacteria are known to have adapted to rapidly changing environmental pressures. The result is a huge chemical and biological diversity among marine Actinobacteria. It is gradually becoming a known fact that, marine Actinobacteria have the capability to produce nanoparticles which have reasonable sizes and structures with possible applications in biotechnology and pharmacology. Mycobacterium sp. BRS2A-AR2 was isolated from the aerial roots of the mangrove plant Rhizophora racemosa. The Mycobacterium was demonstrated for the first time ever to produce AuNPs with sizes that range between 5 and 55 nm. The highest level absorbance of the biosynthesized AuNPs was typical for actinobacterial strains (2.881 at 545 nm). The polydispersity index was measured as 0.207 in DLS and the zeta potential was negatively charged (− 28.3 mV). Significant vibration stretches were seen at 3314, 2358, 1635 and 667 cm−1 in FT-IR spectra. This demonstrated the possible use of small aliphatic compounds containing –COOH, –OH, –Cl and –NH2 functional groups in the stabilization of the AuNPs. The effect of the biosynthesized AuNPs on HUVEC and HeLA cell lines was measured at 48 h. IC50 values were determined at 3500 µg/ml concentration for HUVEC and HeLA cell lines at 45.25 and 53.41% respectively. © 2018, Association of Microbiologists of India.
Keywords: Actinobacteria; Cytotoxicity; Gold nanoparticles; Spectroscopy